GORONTALO STUDENT SPORTS EDUCATION AND TRAINING CENTER - Arief Ibnu Haryanto; Khoirul Anwar Pulungan; Nurkhoiroh Nurkhoiroh; Meri Haryani; Sulasikin Sahdi Kadir (Hanoman Journal: Physical Education and Sport, 2023)
Kicks in pencak silat martial arts certainly need to be given special training by trainers because there are various types of kicks and also the speed varies between movements. This study aims to survey the kick speed of Pesilat Center for Student Education and Training (PPLP) of Gorontalo Province. The research design used in this research is descriptive quantitative research using surveys and test techniques. This study used the entire population of athletes from the Gorontalo Province Student Training Education Center (PPLP), totaling 10 athletes, consisting of 5 male athletes and 5 female athletes. The data collection technique uses a kick speed measuring instrument. As a result, for the front kick, most of them get enough category. Crescent kicks mostly get good categories. While the side kicks mostly get less categories. Trainers should use appropriate training methods. The trainer should follow the training periodization program that has been made starting from the general training stage to the pre-competition in order to have the desired results.